2009
DOI: 10.1038/sj.bjc.6605197
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral neural cell sensitivity to mTHPC-mediated photodynamic therapy in a 3D in vitro model

Abstract: BACKGROUND: The effect of photodynamic therapy (PDT) on neural cells is important when tumours are within or adjacent to the nervous system. The purpose of this study was to investigate PDT using the photosensitiser, meta-tetrahydroxyphenyl chlorin (mTHPC), on rat neurons and satellite glia, compared with human adenocarcinoma cells (MCF-7). METHODS: Fluorescence microscopy confirmed that mTHPC was incorporated into all three cell types. Sensitivity of cells exposed to mTHPC-PDT (0 -10 mg ml -1 ) was determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 24 publications
(32 reference statements)
1
29
0
Order By: Relevance
“…In the case of mTHPC, the potential dark toxic effect is examined for several cell types. Depending on PS concentration, dark incubation time, cell line and drug formulation, the dark toxicity of mTHPC is rated to be low 56–59. Furthermore, it is shown that aPDT is a save procedure for normal adjacent cells of the apical region.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of mTHPC, the potential dark toxic effect is examined for several cell types. Depending on PS concentration, dark incubation time, cell line and drug formulation, the dark toxicity of mTHPC is rated to be low 56–59. Furthermore, it is shown that aPDT is a save procedure for normal adjacent cells of the apical region.…”
Section: Discussionmentioning
confidence: 99%
“…The time interval between Ce6 administration and light delivery was 3 h. Consequently, complete medium was exchanged and light triggered effect was performed using UVA at 320-400 basically as previously described [30,31]using long-wave UVA light (CAMAG, Germany) at k ex = 366 -nm with 2.2 mW/cm 2 providing an energy equivalent to 2.6 J/cm 2 . The irradiation was continuously performed for 20 min, and cells were incubated for 24 h [32]. Cytotoxicity was determined by measurement of cell viability as a function of cellular redox potential as previously reported [33].…”
Section: In Vitro Dark and Photo-induced Cytotoxicity Of Ce6 In Tellimentioning
confidence: 99%
“…Until recently tumor invasion to the carotid artery has been a contraindication to PDT but more recently prophylactic endoluminal carotid stenting has been suggested and might overcome some of these problems . Another big advantage is the apparent lack of nerve damage. While PDT causes cellular death in many cell types, it does not seem to do so in neurons . This is especially important in the head and neck area, where nerve preservation is crucial for function preservation and where the “gold standard treatment” of head and neck cancer often goes along with ablative and reconstructive surgery and chemoradiotherapy. There is usually no drug toxicity, except photosensitivity.…”
Section: Introductionmentioning
confidence: 99%